Effects of ultraviolet aging on the surface properties and tribological performance of polyformaldehyde. Issue 15 (25th December 2016) - Chen, Song; Duan, Haitao; Xu, Haiping; Wei, Lei; Cheng, Bingxue; Jia, Dan; Li, Jian
ABSTRACT: Ultraviolet aging restricts the outdoor application of polyformaldehyde as the friction material. In this work, ultraviolet aging processes were applied to polyformaldehyde specimens and effects of the processes on their surface properties and tribological performance were evaluated. Surface morphology results show that a thin layer of white powder and micro‐cracks with further ramifications in other directions were observed on the surfaces after 400 h of ultraviolet exposure, while it is not detectable for the unaged specimens. Analysis of aging surface indicates that ultraviolet leads to the increase of micro‐cracks and the degree of crystallinity. All the tribological test results demonstrate that with the extension of ultraviolet aging time, (i) the process of damage on polyformaldehyde surface induced by ultraviolet aging is first slowly and faster afterward; (ii) the fluctuation of the friction coefficients of polyformaldehyde/GCr15 rubbing pairs increases; and (iii) the wear rate of polyformaldehyde markedly increase after aging test 400 h. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44684. Abstract :